PRINSIP-PRINSIP/HUKUM PERKEMBANGAN PESERTA DIDIK DAN IMPLIKASINYA TERHADAP PENDIDIKAN - Mukhlis Mukhlis (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
Development is the process of change in growth at a time as a function of maturity and interaction with its environment. In other words, development is a functional change that is influenced by the achievement of the level of physical maturity. This development process can be understood by the existence of several principles / laws, in which the principle / law governs the whole of the development process and is definitely something that is in the development process. Thus, these principles must be understood by all education stakeholders, especially for School Principals and Teachers, because the principles are very urgent in increasing the effectiveness and efficiency of achieving educational goals, including by developing a curriculum or making learning programs that are in accordance with the developmental stages of participants the student.